Fear of Missing Out pada Mahasiswa Pengguna Media Sosial: Bagaimana Peran Dukungan Sosial? - Oktorika, Nurliyana; Pratikto, Herlan; Suhadianto, Suhadianto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the relationship between social support and fear of missing out in college students who use social media. The hypothesis proposed is that there is a negative relationship between social support and fear of missing out in college students. This research design uses correlational quantitative research methods. This study was conducted with participants as many as 110 students who use social media at the Faculty of Psychology, University of August 17, 1945, class of 2019, 2020, and 2021. The instruments used in this study were the fear of missing out scale according to the theory of Przbylski and friends (2013) and the social support scale according to Sarafino and Smith's theory (2011). The data obtained were then analyzed using product moment analysis techniques with the help of SPSS 24 for Windows. Based on the results of data analysis that has been carried out, the results show that there is a positive significant correlation between social support and fear of missing out at rxy = 0.500 at p = 0.000 (p < 0.01). The rejection of the hypothesis in this study shows that social support is quite strongly related to the fear of missing out of students who use social media. The higher the social support, the higher the fear of missing out, and vice versa, the lower the social support, the lower the fear of missing out in students who use social media. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial dengan fear of missing out pada mahasiswa pengguna media sosial. Hipotesis yang diajukan adalah adanya hubungan negatif antara dukungan sosial dengan fear of missing out pada mahasiswa. Desain penelitian ini menggunakan metode penelitian kuantitatif korelasional. Penelitian ini dilakukan dengan partisipan sebanyak 110 mahasiswa pengguna media sosial di Fakultas Psikologi Universitas 17 Agustus 1945 angkatan 2019, 2020, dan 2021. Instrumen yang digunakan dalam penelitian ini adalah skala fear of missing out sesuai dengan teori dari Przbylski, dkk (2013) dan skala dukungan sosial sesuai dengan teori Sarafino & Smith (2011). Data yang diperoleh kemudian dianalisis menggunakan teknik analisis product moment dengan bantuan SPSS 24 for Windows. Berdasarkan hasil analisis data yang telah dilakukan mendapatkan hasil bahwa terdapat hubungan positif yang signifikan antara dukungan sosial dengan fear of missing out sebesar rxy = 0,500 pada p = 0,000 (p < 0,01). Ditolaknya hipotesis dalam penelitian ini menunjukkan bahwa dukungan sosial berkaitan cukup kuat dengan fear of missing out mahasiswa pengguna media sosial. Semakin tinggi dukungan sosial maka semakin tinggi juga fear of missing out, begitupun sebaliknya semakin rendah dukungan sosial maka semakin rendah fear of missing out pada mahasiswa pengguna media sosial.